What Is Hidden in the Small Box? Narratives of Late Antique Roman Palestine in Dialogue - Ḳiperṿaser, Reuven 1960- (2021)
This study is a comparative reading of two distinct narrative traditions with remarkably similar features of plot and content. The first tradition is from the Palestinian midrash Kohelet Rabbah, datable to the fifth to sixth centuries. The second is from John Moschos's Spiritual Meadow (Pratum spirituale), which is very close to Kohelet Rabbah in time and place. Although quite similar, the two narratives differ in certain respects. Pioneers of modern Judaic studies such as Samuel Krauss and Louis Ginzberg had been interested in the question of the relationships between early Christian authors and the rabbis; however, the relationships between John Moschos and Palestinian rabbinic writings have never been systematically treated (aside from one enlightening study by Hillel Newman). Here, in this case study, I ask comparative questions: Did Kohelet Rabbah borrow the tradition from Christian lore; or was the church author impressed by the teachings of Kohelet Rabbah? Alternatively, perhaps, might both have learned the shared story from a common continuum of local narrative tradition? Beyond these questions about literary dependence, I seek to understand the shared narrative in its cultural context.